2020
DOI: 10.3390/ijerph17145222
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Pattern Changes in Nursing Students during the COVID-19 Lockdown

Abstract: The prevalence of poor sleep quality among students is very high and, in nursing students, has been associated with reduced performance, behavioral changes, dietary changes, and even aggressive behavior due to changes in sleep patterns. The lockdown in response to COVID-19 may have resulted in lifestyle changes that affected sleep quality. For this reason, the objective of this study is to determine the difference in nursing students’ sleep quality before and during the lockdown, put in place in response to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
123
6
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 43 publications
22
123
6
8
Order By: Relevance
“…Other studies also found increased sleeping hours during lockdown [ 6 , 32 ]. Nevertheless, a study performed in nursing students found that despite the longer time spent in bed, students’ sleep quality was lower during lockdown [ 33 ]. Similar findings regarding sleep quality were described in working adults and university students from Italy, who reported both going to bed and waking up later, but despite spending more time in bed they reported lower sleep quality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found increased sleeping hours during lockdown [ 6 , 32 ]. Nevertheless, a study performed in nursing students found that despite the longer time spent in bed, students’ sleep quality was lower during lockdown [ 33 ]. Similar findings regarding sleep quality were described in working adults and university students from Italy, who reported both going to bed and waking up later, but despite spending more time in bed they reported lower sleep quality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, response rate may differ in baseline anxiety levels or other factors between responding and non-responding students, which may have resulted in substantial non-response bias in study results. although it must be taken into account that studies on university students have similar limitations (Alzoubi et al, 2020;Romero-Blanco et al, 2020). Therefore, although the results are relevant, they are insufficient in terms of potential generalization.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…This finding corresponds to another study that demonstrates lock down and isolated life exacerbated the mental. In this study, it has been found that women are most vulnerable to post COVID sufferings of women notably [59,60]. On the contrary, another study analyzed few factors responsible for the tendency of the SARS-CoV-2 patients' to commit suicide [61].…”
Section: Discussionmentioning
confidence: 88%